Trends of Reported HIV Sexual Risk Behaviour and HIV Incidence among Fisherfolk in Uganda Receiving Clinic-based Routine HIV Counseling and Testing - Mushabe Bahemuka, Ubaldo; Abaasa, Andrew; Ruzagira, Eugene; Mukasa Kibengo, Freddie; Ndibazza, Juliet; Asiki, Gershim; Mulondo, Jerry; Andrew Price, Matthew; Fast, Patricia; Kamali, Anatoli (AIDS Research and Human Retroviruses, 2014)
HIV counseling and testing (HCT) has been shown to reduce HIV risk behavior and is central to HIV prevention programs. We investigated risk behavior and HIV incidence trends in a fisherfolk cohort on Lake Victoria, Uganda. HIV negative volunteers aged 18–49 years, at high risk of HIV infection and willing to undergo HCT were enrolled. At every quarterly visit, they received HCT. Condoms and STI treatment were also provided. Risk behavior data on alcohol consumption before sex, multiple or new sex partners, condom use and exchange of gifts for sex in the past 3 months were collected at baseline and every 6 months for 2 years. We fitted multilevel logistic regression models to investigate the trends.
Keywords: HIV Sexual Risk Behavior; HIV; Fisherfolk; Uganda; Clinic-based Routine HIV Counseling and Testing